Meta Concept Of Horizon Ilmu And Its Application On Islamic Political Thought Department Of UIN Mataram - Muh. Alwi Parhanudin (Politea : Jurnal Politik Islam, 2021)
This article will analyze the concept of scientific integration-interconnection and internalization or the “Horizon Ilmu” in the Islamic State University of Mataram. This study formulates the implementation model on the curriculum of PPI Department. This article aims to combine Karl Popper's falsification theory, and the theory of paradigm revolution by Tomas Kuhn, with Ian Barbour's theory about the integration between religion and science. As an additional theory on this subject, author use amin abdullah's theory of integration-interconnection. This study uses interpretive approach, that Focuses on the ideas and the spirit and the implementation method that construct the political theory. This study describes conclusions. First, the PPI' s model of Horizon Ilmu, consist two fundamental discourses: the Islamic political thought represented by al-Madinah al-Fadhilah, and the western political science represented by democracy. Second, These two fundamentals then emulsified with the classical islamic scientific tradition. Third, PPI’s characteristic of Horizon Ilmu can be actualized through the reciprocal relation between these two fundamentals discourses in order to build the new academic traditions in the Islamic political thought department.